Research on the Privacy Protection Technology of Blockchain Spatiotemporal Big Data - Bao Zhou; Junsan Zhao; Ying Yin; Guoping Chen (IEEE Access, 2024)
At present, the rapid development of big data technology and the Internet of Things has led to the generation of spatiotemporal data streams on a substantial scale. In this context, data holders often opt for cloud storage of their data to mitigate the pressure of local storage and computing overhead. However, this centralized storage mode renders the data susceptible to risks of tampering and leakage due to the absence of physical control over spatiotemporal big data. Therefore, this paper devises a blockchain-based spatiotemporal big data privacy protection scheme. Initially, to ensure data privacy, the scheme adopts a storage mode where the public and side chains are coordinated. Subsequently, the irreversible SHA256 algorithm is utilized to authenticate the access nodes. Finally, AES and RSA hybrid encryption are applied to encrypt the collected spatiotemporal big data, further enhancing the security of private data. The security performance of the system was evaluated by comparing the success rate of attacks on the blockchain under various circumstances. Additionally, the system throughput of this scheme was analyzed through simulation, revealing that the service life of this system extends to a minimum of 13.79 years when 100 nodes are used. In this context, the system throughput achieves 1607 transactions/s, each node hosts 1.2107 blocks, and querying specific spatiotemporal data takes less than 2 seconds.